Fluid balance and hydration habits of elite female field hockey players during consecutive international matches - MacLeod, H.; Sunderland, C. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this study was to assess sweat loss and hydration practices of elite female field hockey players during consecutive international matches. Eighteen England U21 field hockey players were assessed during 2 consecutive international matches. Sweat loss was assessed from changes in body mass after correction for the volume of fluid consumed and any urine loss. Players completed a questionnaire to assess hydration habits and practices. Mean (± SD) change in body mass after match 1 was -0.1 ± 0.6 kg compared with -0.3 ± 0.5 kg after match 2. This equates to a percentage level of body mass change of -0.2 ± 1.1% after match 1 and -0.5 ± 0.7% after match 2. Mean fluid intake was 1264 ± 394 mL during match 1 and 1216 ± 488 mL during match 2. Prematch urine osmolality was significantly higher before match 2 (425 ± 206 mOsm/kg) compared with match 1 (197 ± 110 mOsm·kg-1; p = 0.008). There was no significant difference between morning body mass changes (p = 0.97); however, 14 players experienced reductions in body mass. There were large interindividual differences in sweat loss and drinking habits in players, ranging from levels of dehydration reaching 2% body mass loss to net body mass gains of 2.4%. Fluid loss was moderate, and players were aware of the impact that dehydration has on performance. With regular substitutions, moderate conditions, and a sound knowledge of correct hydration practice, hydration status was well maintained despite playing consecutive matches.